Best management practices for yield maximization in rainfed castor: Best management practices for yield maximization in rainfed castor - N NALINI; A V RAMANJANEYULU; K MAMATHA; T L NEELIMA; GANURADHA; G SURESH; M VENKATA RAMANA; CH V DURGA RANI (Journal of Oilseeds Research, 2020)
A field experiment was conducted for yield maximisation through best management practices in castor at RARS, Palem during kharif, 2018. The results revealed that adoption of Best Management Practices (BMPs) in rainfed castor resulted in significantly higher growth and yield attributes such as plant height, effective spike length thus significantly higher seed yield (1555 kg/ha) as compared to that of farmers practice. Thus, higher net returns (` 27251/ha) and B:C ratio (1.9) was accrued due to adoption of BMPs.